Internal marketing and employee commitment: Evidence from the Ghanaian banking industry - Narteh, B. (Journal of Financial Services Marketing, 2012)
Attracting the right mix of employees and getting them committed to the goals and objectives of the organization is a major issue facing service organizations. Scholars have recommended that internal marketing is positively associated with employee commitment but little empirical research exists that has examined the relationship between internal marketing and employee commitment especially in the financial services sector. The current study investigated four internal marketing practices - empowerment, rewards, training and development, and communication and their impact on employee commitment in the retail banking industry. Using data from 410 employees of banks in Ghana, the empirical results indicated that, with the exception of communication, the factors are positively associated with employee commitment. The study concludes that in order to influence employee behaviour in the banking industry in Ghana, bank management must implement measures that provide direct benefits to employees. The strategic implications of the findings are discussed in the article. © 2012 Macmillan Publishers Ltd.
Keywords: commitment; communication training and development; empowerment; internal marketing; rewards